Teacher Corrective Feedback VS Cambridge English Write and Improve (CEWI) in Improving EFL Students’ Writing Performance - Puan Tursina; Henny Susanty; Zuhri Efendi (English LAnguage Study and TEaching, 2021)
This study aimed to explore the students’ preference toward teacher’s feedback with different proficiency levels, to describe the most students’ preference in receiving feedback between teacher written feedback and CEWI at different proficiency levels and to figure out the strengths and weaknesses between teacher corrective feedback and CEWI. A qualitative design was chosen to conduct the study. 16 students from department of English education at STKIP Muhammadiyah Aceh Barat Daya in Aceh, Indonesia, were involved in this study. The participants were assigned into two different groups; high proficient students and risk proficient students after receiving the treatments. Students’ essays and semi-structured interviewed were used to collect the data. Data from the interview were coded and classified in a word processor by using NVivo 12 to get the conclusion. The findings showed that (1) all of them had a positive attitude toward the feedbacks because it helped them to improve their writing performance, (2) No matter high proficient students or risk proficient students assumed that most of them preferred teacher corrective feedback to Cambridge English Write and Improve (CEWI). Also, more than 10 students preferred to receive indirect feedback to direct feedback. In addition, teacher corrective feedback could check both global and local errors made by students meanwhile CEWI only focused on the local errors and (3) The strength of teacher corrective feedback was able to ask for the clarification directly and it provided the suggestions for both errors. While, CEWI provided the valuable feedback instantly in their writing. On the other hand, the weakness of teacher corrective feedback was spending a lot of time, while CEWI was only focused on local error and was not able to discuss. In conclusion, a teacher must be able in choosing and providing the appropriate feedback to students. A lot of things must be taken as his or her consideration so the feedback might assist and functional to students’ writing skill. In addition, both of feedback could give students benefit but a teacher’s role is the most important aspect needed by students to help them improving their writing.